Evaluation of Treatment Efficacy of Surgical Interventions for Tubercular Cervical Lymphadenopathy - Bakht Zada, Saadia Nawaz Durrani, Motasim Billah, Javed Iqbal, Ali Khan, Muhammad Nadeem, (Pakistan Journal of Medical & Health Sciences, 2022)
Tuberculosis leads to the most prevalent extrapulmonary problem, which is lymphadenitis. It is quite difficult to diagnose and treat this problem because its ape to several other disorders as well as it is not detectable in physical and lab verdicts. Objective: The purpose of this research work is to assess the part of surgery for tubercular cervical lymphadenopathy for detection and treatment. Study design: It is an observational study with the statistical approach Methods: This work proceeded from January 2021 to June 2022 in the department of ENT, Head & Neck Surgery Lady Reading Hospital Peshawar. The head of the department has given permission for this study work. Total 120 selected patients had some surgery on their necks in the past years. Results: The biopsy of 120 patients was done for the diagnosis of lymphadenopathy. When a lymph node elimination biopsy was done, some of the patients had been diagnosed with tubercular cervical lymphadenopathy. Among these diagnosed patients, a few react to the CAT-1 (ATT), and a few of the patients further need surgery for the excision of the abscess. Some of the patients redevelop the disease after treatment and few patients show no cure after treatment with CAT-1. When this therapeutic treatment of the patients (previously shown the failure of treatment) had been done for the second time, they all responded and showed no illness. Conclusion: For the diagnosis of tubular lymphadenopathy, surgical intrusion plays a role and anti-tubular therapy is an effective method of treatment but surgical intrusion is mandatory. Patients having more complicated issues get rid of these issues after this treatment. This treatment led to the enhanced life span of the patient. Keywords: Biopsy, Tuberculosis, CAT-1, ATT, Surgical treatment